The Coefficient of Variability is the Same in the mTOR-inhibitors?. (July 2018) - Valero, Rosalia; Sanchez-Fructuoso, Ana; Rodrigo, Emilio; Perez-Flores, Isabel; De Cos, M Angeles; Belmar, Lara; Delgado, Jesus; San Millan, Juan Carlos Ruiz
Abstract : Background: Intrapatient trough levels variability of immunosuppressive drugs must be considered as a prognostic factor. Many studies demonstrate the relationship between the high intrapatient variability of calcineurin inhibitors (CNI) levels and poor long-term renal graft outcome. Recent studies suggest a lower variability when using once-daily tacrolimus compared to the classical twice-daily formulation. Our objective is to analyze the intrapatient variability observed in the blood levels of mTOR-inhibitors (mTORi) and to compared the variability of sirolimus (SRL) with that of everolimus (EVL) in transplant patients converted to an iMTORi. Methods: We analyzed 256 adult renal transplant patients converted to an mTORi between Jan-2009 and Dec-2015 in two Spanish transplant centers. The mean post-transplant conversion time was 51, 6 months. One hundred and seventeen werw converted to SRL and 139 to EVL. Coefficient of variation (CV) was calculated using at least 3 blood trough levels between 3 and 18 months postconversion. Conversions in the first postransplant year (121) and later (135) were analized separatedly. CV was correlated with graft evolution (graft survival and/or renal function). Results: The mean and median CV of the entire group was 25, 6∓13, 0% and 23, 7∓12, 1%. SRL and EVL mean CV was 23, 8% and 27, 1% (p=0, 04). Inthe subgroup of late conversions (>1 y) SRL and EVL-CV was 23, 0% and 29, 0% (p=0, 008). 59, 8% vs 41, 7% of patients converted to SRL and EVL respectively had a CV below the median (p=0, 004). No differences in graft evolution could be demonstrated between patients with high and low CV at a mean follow-up of 58, 5∓21, 4 months. Conclusions: We suggest that SRL has a lower CV than EVL. This difference should probably have a prognostic significance but we have not found differences in the long-term follow-up. This might probably be a consequence of that most patients were converted in the stable postransplant phase.